Living Tradition Of Hadhrami Sufism: Ethical Actualization Of Al-Haddadiyyah Teachings In Indonesian Islamic Boarding Schools - Choirul Anam; M. Khusna Amal; Sofkhatin Khumaidah; Moh. Ferdi Hasan (FALASIFA : Jurnal Studi Keislaman, 2026)
The globalization of Islamic traditions through diaspora movements presents a unique opportunity to examine how classical Sufi teachings adapt to contemporary socio-religious contexts. This study investigates the actualization of Al-Haddadiyyah Sufi ethics within Indonesian Islamic boarding schools (pesantren), focusing on how Abdullah bin Alawi Al-Haddad's six core humanistic values explicitly articulated in his works, particularly Nasaih al-Diniyah and Risalat al-Muawanah are transmitted, interpreted, and practiced in daily educational life. Through qualitative field research in three pesantren in East Java, Indonesia, this study explores: (1) the pedagogical mechanisms of transmitting Al-Haddad's ethical teachings, (2) the manifestation of six core humanistic values in pesantren community life, and (3) the synthesis between classical Sufi wisdom and modern educational challenges. Data were collected through participant observation, in-depth interviews with kyai (religious leaders), ustadz (teachers), and santri (students), and documentation analysis. Findings reveal that Al-Haddadiyyah ethics are not merely preserved as textual heritage but are dynamically actualized through habitual practices (ta'wid), communal rituals (majalis), and interpersonal relationships. The values of kaff al-adza (non-harm), al-mu'awanah (mutual assistance), al-shohbat (companionship), al-'adlu (justice), al-rifq (gentleness), and al-tasamuh (tolerance) function as living ethical frameworks that address contemporary issues such as bullying, intolerance, and moral degradation among youth. This research contributes to Islamic Civilization studies by demonstrating how Hadhrami Sufi traditions maintain their relevance through adaptive transmission while preserving their essential spiritual-ethical core, offering insights into the enduring vitality of Islamic educational traditions in modern contexts.